INFLUENCE OF CONSTRUCTIVE AND TECHNOLOGICAL DEFECTS ON DURABILITY OF REINFORCEMENT BARS - Y. V. Vasilevich; L. E. Reut; А. M. Yaznevich (Наука и техника)
The paper contains calculation on durability of a reinforcement bars with a constructive and technological defect. The factors determining constructive and technological durability of reinforcing bars have been investigated in the paper. The paper demonstrates classification of reinforcement bar parts in accordance with danger of constructive and technological influences.